Peningkatan Kemampuan Menulis Teks Berita melalui Metode Quantum Learning dengan Media Gambar Siswa Kelas VIIIE SMP Negeri 17 Surabaya - Tri Indriaty (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The purpose of this study is to determine the ability to write news text through the method of quantum learning by using the image media on the students of class VIIIE SMP Negeri 17 Surabaya. To achieve the objectives of research required instruments include: teacher activity observation sheets, student activity observation sheets, and student learning outcomes. The data obtained in this study is presented in table form and analyzed by description. Implementation of learning carried out in three learning cycles and in each cycle showed the increase of teacher activity and activity, the average value of students in each cycle also showed an increase in the number of average values, in the first cycle learning the average value of students is 62.92, the average of students in the second cycle of learning is 72, in the third cycle of learning is 80, so learning news writing through quantum learning method with the first cycle image media up to the third cycle shows the increase in the average value of students. Keywords: Writing Text News, Quantum Learning, Picture Media.